2011
DOI: 10.1016/j.jpag.2010.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Familial, Cultural and Psychosocial Influences of Use of Effective Methods of Contraception among Mexican-American Adolescents and Young Adults

Abstract: Study Objective To compare culturally relevant factors associated with ever having used an effective method of contraception among a cohort of predominantly Mexican American females. Design Face to face interviews were conducted in either English or Spanish. The survey used was developed directly for this study based on qualitative research with this population as well as the existing literature. Women were grouped as either adolescents (ages 13–20) or young adults (ages 21–25) for study purposes. Setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 27 publications
(32 reference statements)
5
54
1
Order By: Relevance
“…At the cultural level, less acculturated participants reported more sexual risk, which was contrary to hypothesis. This finding is consistent with studies of samples of US-born Latina women and Latinas who lived in the US for decades (Gilliam et al, 2011; Moreno et al, 2011). Much literature has documented complex relations between acculturation, time in the US, and sexual risk: Recently immigrated Latino youth were more likely to be sexually active if they were less acculturated, whereas US-born or longer residing immigrant youth tended to be sexually active if they were more acculturated (Guilamo-Ramos, Jaccard, Pena, & Goldberg, 2005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At the cultural level, less acculturated participants reported more sexual risk, which was contrary to hypothesis. This finding is consistent with studies of samples of US-born Latina women and Latinas who lived in the US for decades (Gilliam et al, 2011; Moreno et al, 2011). Much literature has documented complex relations between acculturation, time in the US, and sexual risk: Recently immigrated Latino youth were more likely to be sexually active if they were less acculturated, whereas US-born or longer residing immigrant youth tended to be sexually active if they were more acculturated (Guilamo-Ramos, Jaccard, Pena, & Goldberg, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…However, greater acculturation also has been related with more condom use (Gilliam, Neustadt, Whitaker, & Kozloski, 2011). According to cultural norms theory (Afable-Munsuz & Brindis, 2006), Latina immigrants may be exposed to more permissive US sexual norms and acculturate to them over time.…”
Section: Cultural-level Macrosystemic Factorsmentioning
confidence: 99%
“…Furthermore, racial-ethnic disparities persist, with disproportionately higher rates of pregnancy and birth among African American and Latina teenagers compared to Whites (Guttmacher Institute 2014). Although a significant proportion of teenage pregnancies are terminated, the birth rate among Latina teenagers remains the highest of all racial-ethnic groups and is twice that of non-Hispanic White teenagers (Braveman and Brindis 2011 Denner et al 2001;Gilliam 2007;Gilliam et al 2011;Minnis et al 2013;Schwartz et al 2011; for a substantive critique of the literature, see Geronimus 1997). Less attention has been paid to what happens during the time in between the discovery that one is pregnant and the decision to carry that pregnancy to term and become a parent.…”
Section: Adolescent Pregnancy Resolutionmentioning
confidence: 99%
“…While previous studies have not substantively explored pregnancy resolution among Latina teenagers, the role of cultural values in shaping sexual and reproductive behaviour among Latina/o young people has been examined more generally (Denner et al 2001;Erickson 1998;Gilliam et al 2011;Kaplan et al 2001;Minnis et al 2013;Raffaelli and Ontai 2001;Russell and Lee 2004;Schwartz et al 2011;Villarruel 1998 Villarruel 1998). Cultural values such as familismo and respeto as well as adherence to traditional gender ideology are strong themes within the literature.…”
Section: Latina/o Teenage Sexualitiesmentioning
confidence: 99%
“…Some of those studies measure acculturation as a multidimensional process that implies changes in believes, attitudes and values (Thomson and Hoffman-Goetz 2009;Wallace et al 2010). Almost all studies found that more acculturated Latino youth -measured by multidimensional scales that include nativity, language use, language and media preference, generation, ethnic identity, cultural orientation and behaviours and interactions -report initiation of sexual intercourse at an earlier age and are more likely to use contraception compared with less acculturated youth, and that this association persists even after adjustment for socioeconomic variables (Afable-Munsuz and Brindis 2006; Gilliam et al 2011;McDonald, Manlove, and Ikramullah 2009;raine, Minnis, and Padian 2003).…”
mentioning
confidence: 99%